Effect of Bamboo Leaf Litter Mulch on Weed Suppression of Sweet Corn (Zea mays saccharata Sturt) - Anuar Ramut; Deden Sumoharjo; Muhammad Husaini Assauwab; Irfan Apandi; Rahmat Barona; Mario Pani; Era Maulia; Maulana Zubir; Yulis Untari; Vinny Pratiwi; Rahmi Aurya Bella (Warmadewa University Press, 2026)
The issue of weed competition becomes increasingly critical in sweet corn cultivation when weeds are not controlled during the early stages of crop growth. This study aimed to determine the appropriate application rate of bamboo leaf litter mulch for effective weed suppression while simultaneously enhancing the growth and yield of sweet corn. The experiment was conducted within the experimental area of the Faculty of Agriculture, Universitas Gunung Leuser, Kutacane, Aceh Province, Indonesia. The experiment was arranged using a non-factorial Randomized Complete Block Design (RCBD) consisting of three treatment and three replications. The treatments were defined as D0=0, D1=2, D2=4 kg m?¹ of bamboo leaf litter mulch, which correspond to 0, 20, 40 t ha?¹, respectively. The observed variables included weed control percentage, weed cover, number of weed species, weed population density, and fresh weed biomass. Crop growth parameters were also recorded, including plant height, stem circumference, and number of leaves at 10, 20, 30, and 40 DAP. Yield-related parameters consisted of ear diameter, ear length, ear weight, kernel weight, and dry shelled grain yield. Application of bamboo leaf litter mulch at 20 t ha?¹ effectively enhanced weed control percentage at 10 and 20 DAP, while reducing weed cover percentage at 10, 20, and 30 DAP, as well as decreasing weed fresh weight at 20 DAP. Furthermore, this treatment promoted sweet corn growth by increasing plant height at 20 and 40 DAP, leaf number at 30 DAP, and improving cob length, cob weight, and grain yield of sweet corn.